2022
DOI: 10.3390/biomedicines10010133
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Hyperlipidemia: Association with Inflammation and Subclinical Atherosclerosis in Patients with Rheumatoid Arthritis

Abstract: Objective: To describe postprandial lipidemia in patients with rheumatoid arthritis (RA) and to analyze its association with subclinical atherosclerosis and inflammatory activity. Methods: Observational study of 80 cases of RA and 80 sex- and age-matched controls. We excluded individuals with dyslipidemia. Postprandial hyperlipidemia (PPHL) was defined as postprandial triglycerides >220 mg/dL and/or postprandial ApoB48 levels >75th percentile (>p75). Plasma lipids, cholesterol, triglycerides, ApoB48, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Uslu Yurteri et al 9 study failed to document such relation. In support of our conclusions, elevated CRP levels were frequently linked to SCA in many clinical conditions including rheumatoid arthritis, 20 newly diagnosed diabetes 21 and psoriasis. 22 In our work, endocan levels were significantly elevated in BD patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 89%
“…Uslu Yurteri et al 9 study failed to document such relation. In support of our conclusions, elevated CRP levels were frequently linked to SCA in many clinical conditions including rheumatoid arthritis, 20 newly diagnosed diabetes 21 and psoriasis. 22 In our work, endocan levels were significantly elevated in BD patients as compared to healthy controls.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, nearly 8% of all disease burden in developed countries is due to elevated blood cholesterol [ 10 ]. In addition, several studies have shown that hyperlipidemia and inflammation are closely interconnected and have a significant contribution to certain cardiovascular diseases such as atherosclerosis [ 14 , 15 ]. A recent study has shown that blockade of interleukin (IL)-1b reduces the incidence of cardiovascular events in patients diagnosed with myocardial infarction and C-reactive protein levels > 2 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…131 Mena-Vázquez et al found that PPHL in RA patients was significantly associated with subclinical atherosclerosis, TNF-α, and high-sensitivity C-reactive protein, suggesting that PPHL in RA is associated with inflammation and subclinical atherosclerosis. 95 Other studies have also found that cIMT is associated with postprandial ApoB48 and total ApoB, providing evidence that atherogenic chylomicron remnants contribute to atherosclerosis in RA. 103,132 Biomarkers associated with bone turnover such as osteoprotegerin (OPG) have been associated with CAC, carotid plaque, and IMT.…”
Section: The Role Of Endothelial Dysfunctionmentioning
confidence: 89%